Corporate Social Responsibility as Strategy in Indonesia Context - Sinaga, Rifeald Romauli (Universitas Prasetiya Mulya, 2024)
This paper discussing Corporate Social Responsibility as part of company’s strategy in Indonesia context as CSR become mandatory since 2007 through Company Act No. 40. However, to date there are a lot of companies not taking advantage of CSR program by integrating it into company’s strategy. Using qualitative methods, particularly a systematic literature review, this article outlines the debates that currently exist in CSR area before suggesting tools for CSR strategy. The result indicates the importance of stakeholders for the creation of CSR program. Therefore, a company should first identify and rank the stakeholders from the most important to the least important. Then, a company should create a stakeholder mapping as a guidance in creating CSR part of the strategy.